Legitimate Interest of Coastal States in Seabed Mining: Indonesia’s Practice - Puspitawati, Dhiana; Susanto, Fransiska Ayulistya; Rusli, Mohd Hazmi Mohd; Fadli, Moh. (Hasanuddin Law Review, 2023)
This paper focuses on the utilization of sea mineral resources in areas within national jurisdiction and in the international seabed area (hereafter known as the Area). It discusses Indonesian laws relevant to seabed mining and the need for such laws to take into consideration the maritime zones and activities in the Area, as stipulated by UNCLOS 1982. This paper begins with the identification of potential sea minerals both within national jurisdiction and in the Area. Next, it analyzes the international legal framework on seabed mining, including a discussion on the meaning of "legitimate interests of coastal States" and on the participation of developing states in the Area, as stipulated in Article 142 and 148 of UNCLOS 1982. Then, the national legal framework relating to seabed mining is discussed. Using the juridical-normative method, this paper finds that Indonesia does not currently have comprehensive national regulations covering seabed mining within its jurisdiction and in the Area. Although there is a presidential decree on the exploitation of sea sand, it is limited to institutional arrangements and only focuses on sea sand. Thus, this paper recommends the formulation of national regulations regarding the use of the seabed, both within and beyond national jurisdiction.